KESEPADANAN PENERJEMAHAN DEIKSIS I KE DALAM BAHASA INDONESIA PADA NOVEL TO KILL A MOCKINGBIRD - Tapilatu, Terweline; Lewaherilla, August (DINAMIS, 2023)
This qualitative research aims at understanding how first person deixis ‘I’ is translated into Indonesian and in what ways it differs from its equivalents. The method used is content analysis. The data were collected using purposeful sampling from the English novel To Kill a Mockingbird by Harper Lee and its Indonesian translation. The findings reveal that deixis ‘I’ was translated into deixis ‘saya’, ‘aku’, ‘ku-‘ and ‘-ku’ which are in the pronominal category and the kinship term ‘ibu' which belongs to the noun category. ‘I’ was also translated into phrases, adverbs, adjectives, nouns, second person deixis ‘you’ which was ellipsed, and ‘I’ which was not translated into the target language. Deixis ‘I’ differs from ‘saya’, ‘aku’, ‘ku-’, ‘-ku’ and ‘ibu’ in social relations between the speaker and the addressee, their social status, the speech context, and the cultural background of both texts. Other equivalents are different from ‘I’ in terms of their status as non-deictic expressions. The use of various forms of equivalent aside from ‘saya’, ‘aku’, and ‘ku-’, either deictic or non-deictic, indicates that the results of translation are not always predictable. The reason for using those equivalents is to maintain the acceptability and naturalness of the target text. To maintain equivalence between both texts, certain procedures or strategies are applied, i.e., unit shifts, class shifts, modulation, and translation by omission. This research may contribute to enriching translation studies, in particular of deixis, by providing information about the translation of first person deixis ‘I’ into Indonesian.